A mechanistic framework for understanding prairie stream fish distributions - Troia, Matthew John (Kansas State University, 2014)
A fundamental goal of ecology is to understand environmental associations of species. These associations can provide a basis for predicting spatial distributions in contemporary habitats as well as how those distributions might change in response to anthropogenic environmental change. Developing species distribution models is limited by an incomplete understanding of functional traits, spatial scaling, and the mechanisms and generalities of correlations among abundance and environmental gradients. I address these four issues using observational and experimental approaches. First, I tested opposing mechanisms of community assembly by measuring the dispersion (i.e., diversity) of three types of functional strategies at three spatial scales and along environmental gradients. I found that communities are assembled via abiotic environmental filtering, but the strength of this filtering depends on the spatial scale of investigation, longitudinal network position, and type of functional strategy. Second, I quantified community-environment relationships across thirteen sub-basins, nested within the three major basins within Kansas to evaluate the consistency (i.e., generality) in predictive capability of environmental variables among sub-basins and across spatial extents. I found that longitudinal network position is consistently the strongest predictor of community composition among sub-basins, but in-stream and catchment predictors become stronger correlates of community composition with increasing spatial extent. Third, I used environmental niche models to quantify distributions of four pairs of congeneric cyprinids and found that species within each pair exhibited contrasting stream-size preferences. I then used field experiments to test for differences in individual-level performance between one pair of species (Pimephales notatus and P. vigilax) along a gradient of stream size. I found that adult spawn success and juvenile growth and condition increased with stream size for both species, indicating that these congeners respond similarly to abiotic gradients associated with the river continuum. I concluded that complementary distributions are a consequence of biotic interactions, differential environmental filtering evident in an unmeasured performance metric, or differential environmental filtering by an environmental factor operating at longer timescales. These studies demonstrate the context dependencies of characterizing habitat associations of stream fishes, but also reveal the general importance of stream size and associated environmental gradients in structuring stream fish communities.
Keywords: Fish ecology; Community ecology; Environmental niche modeling; Ecology (0329)